2021
DOI: 10.1016/j.psep.2021.06.040
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on environmental presence of pharmaceutical drugs tested for the covid-19 treatment

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 189 publications
(197 reference statements)
0
25
0
Order By: Relevance
“…Pollution clean-up is concerned with decreasing the levels of pharmaceuticals in environmental matrices after a contamination event. Wastewater treatment plants are the most used pollution clean-up approaches (Ramiro et al 2021 ; Abhradeep et al 2021 ). The removal efficiency of COVID-19 related pharmaceuticals is low following primary and secondary treatment, but can be high following tertiary treatment.…”
Section: Ecotoxicologymentioning
confidence: 99%
“…Pollution clean-up is concerned with decreasing the levels of pharmaceuticals in environmental matrices after a contamination event. Wastewater treatment plants are the most used pollution clean-up approaches (Ramiro et al 2021 ; Abhradeep et al 2021 ). The removal efficiency of COVID-19 related pharmaceuticals is low following primary and secondary treatment, but can be high following tertiary treatment.…”
Section: Ecotoxicologymentioning
confidence: 99%
“…In both studies, antivirals against HIV and Hepatitis B virus were the most widely used antivirals. On the other hand, the pandemic due to COVID-19 increased the consumption of antivirals such as remdesivir, oseltamivir, favipiravir, remdesivir among others and antiparasitics such as ivermectin [12,42].…”
Section: Human Medicinementioning
confidence: 99%
“…In this context, Bortone et al [11] reported an increase in antimicrobial consumption of 65% between 2000 and 2015. Recently, the pandemic due to COVID-19 has dramatically favored the large-scale use of a group of antimicrobials for therapeutic purposes (azithromycin, ivermectin, remdesivir, favipiravir, among others) [12]. Therefore, monitoring of antimicrobial drugs is necessary for the development of guidelines to enable their regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Once HCQ has a high potential to persist, bioaccumulate, and transfer to living organisms, even in small quantities, the concern becomes greater, given the large amount of wastewater contaminated with hydroxychloroquine, which can reach aquatic matrices, persisting in the environment and causing damage to living beings (Dabić et al, 2019 ; Gosu et al, 2016 ; Howard and Muir, 2011 ; Ramesh et al, 2018 ). This perspective leads to studying efficient and low-cost processes that can eliminate these compounds (Nippes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%